Secure and Efficient IP Mobility Support for Aeronautical Communications - Bauer, Christian (KIT Scientific Publishing, 2013)
Motivated by the future Internet Protocol (IP) based aeronautical telecommunications network supporting air traffic control communications, this thesis specifies a route optimization protocol for Network Mobility (NEMO) that is both secure and efficient.Furthermore, a new certificate model is defined that is particularly suitable for the aeronautical environment.The improvements of the new concepts in terms of security and efficiency are demonstrated and compared to the state of the art.